Pengaruh penambahan tepung darah pada pakan terhadap konsumsi pakan, pertambahan bobot badan, konversi pakan serta umur pertama kali bertelur burung puyuh - Johan Wahyu Utomo; Edhy Sudjarwo; Adelina Ari Hamiyanti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
This study was conducted to evaluate the use of blood meal in ration on quail’s feed consumption, body weight gain, feed conversion ratio and age at first laying. Materials for this reseach were 120 quails. The method of the study was experimental research with 4 treatments and 6 replications. The treatments consisted of P0 = basal feed without blood meal, P1 = basal feed with 4% of blood meal, P2 = basal feed with 8% of blood meal and P3 = basal feed with 12% of blood meal. The variables were feed consumption, body weight gain, feed conversion ratio and age at first laying. Data were analyzed by ANOVA and if there were significant differences among variables it would be tested by Duncan’s multiple range test. The study showed that the treatments had highly significant effects (P<0,01) on quail’s feed consumption and feed convertion ratio and had significant effects (P<0,05) on quail’s body weight gain and age at first laying. The study concluded that the use of 4% of blood meal in quail’s ration had the best result on body weight gain, feed convertion ratio and age at first laying.  Keywords : blood meal, feed consumption, body weight gain, feed conversion ratio, age at first laying, quail